Poly-l-lactic acid microspheres delay aging of epidermal stem cells in rat skin - Dong, Yunxian; Zhang, Youliang; Yu, Hao; Zhou, Lingcong; Zhang, Yaan; Wang, Haibin; Hu, Zhicheng; Luo, Shengkang (Frontiers in Immunology, 2024)
Intradermal injectable fillers offer a wider range of options for cutaneous anti-aging and facial rejuvenation. PLLA microspheres are increasingly favored as degradable and long-lasting fillers. The present study focused solely on the effect of PLLA on dermal collagen, without investigating its impact on the epidermis. In this study, we investigated the effects of different concentrations of PLLA microspheres on epidermal stem cells (EpiSCs) in vitro through culture, and identification of primary rat EpiSCs. The results obtained from CCK-8 detection, apoptosis staining, flow cytometry, Transwell assay, wound healing assay, q-PCR analysis, and immunofluorescence staining collectively suggest that PLLA microspheres promote cell proliferation and migration while delaying cell senescence and maintaining its stemness. Furthermore, in vitro, the mesodermal injection of PLLA microspheres in the rat back skin resulted in delayed aging, as evidenced by histological and immunohistochemical staining of the skin at 2, 4, and 12 weeks of follow-up. This study showed the positive effects of PLLA on rat epidermis and EpiSCs, while providing novel insights into the anti-aging mechanism of PLLA.